PEMBENTUKAN MODEL SPASIAL DATA PANEL FIXED EFFECT MENGGUNAKAN GUI MATLAB (Studi Kasus : Kemiskinan di Jawa Tengah) - Irawati Tamara; Dwi Ispriyanti; Alan Prahutama (Jurnal Gaussian, 2016)
Regression analysis is an analysis of the dependence of one dependent variable, on one or more independent variables. The spatial panel data model is regression models used to explain the effects of region's dependence (spatial effect) and the effect of time period (panel effect) on an observed variable. The establishment of spatial panel data models can be made by an application created using Matlab software called GUI (Graphical User Interface). This research is focus on creating GUI Matlab and the establishment of a spatial panel data model by fixed effects on the case of poverty in Central Java. The results of analysis by using GUI shows that the fixed effects spatial lag model and fixed effects spatial error model are significant. Based on the criteria of goodness of fit, it is known that the fixed effects spatial lag model has higher R2 value than the fixed effects spatial error model that is 0.9903, thus the model chosen as the model of the case of poverty in Central Java is the fixed effects spatial lag model by the spatial lag coefficient is 0.4060. Keywords : GUI, spatial, panel data, fixed effects, fixed effects spatial lag, fixed effects spatial error